New host records for Anenterotrematidae, Lecithodendriidae and Urotrematidae trematodes in bats from Argentina, with redescription of Anenterotrema liliputianum - Lunaschi, Lía Inés (2010)
Anenterotrema liliputianum (Travassos, 1928) (Anenterotrematidae) is redescribed based on the type specimens from Molossus molossus (Pallas) and Phyllostomus elongatus (Geoffroy) from Brazil, and also on new specimens collected from the Dwarf Dog-faced Bat, Molossops temminckii (Burmeister) (Molossidae) in Argentina. In addition, we report the fi nding of Gymnoacetabulum talaveraensis (Lunaschi, 2002), Ochoterenatrema labda Caballero, 1943 (Lecithodendriidae), and Urotrema scabridum Braum, 1900 (Urotrematidae) parasitizing Vespertilionidae and Molossidae bats from Buenos Aires and Misiones provinces, and measurements, prevalence, and mean intensity for these trematodes are provided. In addition, the host spectrum and distribution for A. liliputianum and O. labda is increased, and U. scabridum is recorded for the fi rst time parasitizing bats in Argentina.